Further enhancement of jump point search algorithm applied in pathfinding in a cave explorer - Jade Anne M. Somosa. 4 0 16; 5 (2019)
u
Thesis: (BSCA major in Computer Science) -Pamantasan ng Lungsod ng Maynila, 2019.
Keywords: 2 -- 0; 6; 20; 20; 2